Integration of the Theory of Planned Behavior (TPB) and Theory of Financial Planning Behavior in MSMEs Actors - Achmad Murdiono; Fadia Zen; Subagyo Subagyo (CV. Proaksara Global Transeduka, 2025)
This study aims to integrate the Theory of Planned Behavior (TPB) and behavioral finance theory to explain financial planning behavior among Micro, Small, and Medium Enterprises (MSMEs). Using a descriptive quantitative approach, data were collected through a survey of 399 MSME actors in Malang District and Batu City. The research instruments were developed based on indicators from TPB (attitude, subjective norm, perceived behavioral control) and behavioral finance theory (financial literacy and mental accounting). The results of the descriptive statistical analysis show that the majority of respondents have a moderate level of financial literacy, a positive attitude toward financial planning, but relatively low perceived behavioral control. In addition, it was found that mental accounting behaviors such as present bias tend to influence daily financial decision-making. These findings indicate that integrating TPB and behavioral finance theory provides a more comprehensive understanding of MSMEs' financial planning behavior. The conclusion of this study confirms the importance of a holistic and behavior-based approach in designing educational interventions and appropriate financial policies, particularly to improve the quality of financial decision-making among MSME actors.